Giant cell tumour with intra-articular extension: a case report - Dhanaraj, Gokul Raj; Babu, Siddharth Ramesh; Rajendran, Balaji (International Journal of Research in Medical Sciences, 2017)
Giant cell tumour is usually a benign but locally aggressive tumour. Intra-articular extension of giant cell tumour is rare. Treatment options are limited in such cases. I present here a 33 year old male with a history of swelling around his right knee for 6 months. Patient was diagnosed clinically, radiologically and histologically as giant cell tumour. Patient was treated by surgical excision of the tumour and reconstruction with custom mega prosthesis.